Profil Kemampuan Representasi Siswa Dalam Memecahkan Masalah Matematika Ditinjau Dari Gaya Belajar - Aula Amalia; Nurina Happy; FX Didik Purwosetiyono (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2021)
This study aims to determaine the profile of the representation ability of juniorhigh school students in terms of learning styles. This type of research wasdescriptive qualitative research. The subjects taken were three junior highschool students of eight grade, each of whom had a visual learning style, andauditory learning style, and kinesthetic learning style. The data was collectedusing a learning style scale, written tests, interviews and documentation. Thedata analysis technique was carried out in 3 stages, reduction, datapresentation, and drawing conclucions or verification. The validity of the dataused time triangulation, comparaing the results of the representation abilitytest with the results of interviews in the first and second stages. The analysiswas developed based on indicators of representational ability by taking inroaccount student learning styles. Based on the results of the analysis, it isknown that subjects with visual, auditory and kinesthetic learning styles havelow verbal representation abilities.